The effect of new dynamic splint in pinch strength in De Quervain syndrome: a comparative study. (4th July 2017) - Nemati, Zahra; Javanshir, Mohammad Ali; Saeedi, Hassan; Farmani, Farzad; Aghajani Fesharaki, Siamak
Abstract: Objective For patients with De Quervain syndrome using thumb spica orthosis is restricting, so many patient are dissatisfied with using static model. The aim of this study is to compare the effect of modified dynamic and conventional static orthoses on pinch power and functional abilities of hand in De Quervain syndrome.Method In this quasi-experimental study, palmar and lateral pinch strength of the thumb, pain and functional abilities of hand, patient's satisfaction of orthoses, were evaluated after using modified dynamic and conventional static orthosis in two groups.Results Both orthoses improved palmar and lateral pinch strength of the thumb, pain level and functional abilities. In comparison of mentioned variables, there was no significant difference between two groups regarding to pain recovery and abilities improvement ( p  > 0.05). However, the satisfaction level of the patients who had used dynamic orthosis was higher ( p  < 0.05).Conclusion It seems, adding a joint to the static thumb spica leads to patient's relief and consequently to their satisfaction. Implications for Rehabilitation: The dynamic thumb spica, is easier to use and patients satisfaction is higher than static thumb spica. Therefore, it can be used for conservative treatment of De Quervain syndrome.